The role of SIRT1 level and SIRT1 gene polymorphisms in optic neuritis patients with multiple sclerosis - Kubiliute, Aleksandra; Gedvilaite, Greta; Vilkeviciute, Alvita; Kriauciuniene, Loresa; Bruzaite, Akvile; Zaliuniene, Dalia; Liutkeviciene, Rasa (Orphanet journal of rare diseases, 2023)
To investigate the role of Sirtuin 1 (SIRT1) level and SIRT1 (rs3818292, rs3758391, rs7895833) gene polymorphisms in patients with optic neuritis (ON) and multiple sclerosis (MS). 79 patients with ON and 225 healthy subjects were included in the study. ON patients were divided into 2 subgroups: patients with MS (n = 30) and patients without MS (n = 43). 6 ON patients did not have sufficient data for MS diagnosis and were excluded from the subgroup analysis. DNA was extracted from peripheral blood leukocytes and genotyped by real-time polymerase chain reaction. Results were analysed using the program "IBM SPSS Statistics 27.0". We discovered that SIRT1 rs3758391 was associated with a twofold increased odds of developing ON under the codominant (p = 0.007), dominant (p = 0.011), and over-dominant (p = 0.008) models. Also, it was associated with a threefold increased odds ofON with MS development under the dominant (p = 0.010), twofold increased odds under the over-dominant (p = 0.032) models and a 1.2-fold increased odds of ON with MS development (p = 0.015) under the additive model. We also discovered that the SIRT1 rs7895833 was significantly associated with a 2.5-fold increased odds of ON development under the codominant (p = 0.001), dominant (p = 0.006), and over-dominant (p < 0.001) models, and a fourfold increased odds of ON with MS development under the codominant (p < 0.001), dominant (p = 0.001), over-dominant (p < 0.001) models and with a twofold increased odds of ON with MS development (p = 0.013) under the additive genetic model. There was no association between SIRT1 levels and ON with/without MS development. SIRT1 rs3758391 and rs7895833 polymorphisms are associated with ON and ON with MS development.